ASSESSMENT KLASTER PERIKANAN (Studi Pengembangan Klaster Rumput Laut Kabupaten Sumenep) - ZULHAM, ARMEN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 3 November 2007)
Cluster is the strategy for regional development to support local economic potency. The opinion of fisheries cluster will be developed closed to that strategy, with the aim to establish of fisheries industrial complex. In the fisheries cluster complex, the industrial units encourage to foster the harmonize link among others to increase the economic growth. Research concerning seaweed cluster was conducted in Sumenep (Madura) in May 2007. The location was choice as the target area for the establishment the fisheries cluster complex. The purposes of this research were: i). to identify and study the fisheries industrial cluster complex characteristics related to the development of fisheries industry. ii). To study the characteristic and pattern linkages among industrial units in fisheries center related to institutional development. iii). to generate suggested recommendation for seaweed cluster industrial complex in Sumenep district. Data were collected through survey in the respected area; the respondents covered the local government officers, seaweed farmers, seaweed processors, local traders, exporters, local transportation services and local leaders. The research findings are: there are many seaweed industry units in Sumenep which can be use as the main component to organize for the establishment the seaweed industrial cluster complex, there exist the horizontal conflict among traders and seaweed processors to have the seaweed from the farmers. On the other hand the vertical relationship among industrial unit tends to make asymmetric information on price and product criteria between traders and seaweed farmers. This research recommended the seaweed cluster industrial complex in Sumenep develop based on: consumer oriented, collective and cumulative approach. And the development of Sumenep’s seaweed cluster need three step, namely: preparation step, consolidation step and independency / transfer step. There are two types of industries which can be as a core of the seaweed clusters in Sumenep, there are the seaweed chip industry or the seaweed chip and powder industry.
Keywords: Cluster, Seaweed, Business Relationship, Sumenep.